Géometrie Et Arts-Graphiques Pour Les Pprentissages Fondamentaux A L’ecole Elementaire - Koutou, Kadjo (European Scientific Journal, ESJ, 2017)
Geometric activities are a great way for children, especially those in elementary school, to enter into the mathematical world. To handle, discover, invent, recognize, and identify progressively geometric forms, the child is required to play in space and time with multiple tools and material in order to create new and representative forms. The results obtained have high performance and it helps the teacher to achieve some objectives in all domain of learning, and in particular in the acquisition of transversal skills such as writing and reading. Our suggestions set out ways of improving the objectives set in relation to the undeniable importance of the use of geometric shapes in the practice of graphic art in elementary schools.